Boost employee confidence and inclusion by creating voice space - Philip, Bejoy; Kaminstein, Dana (MIT Sloan Management Review, 2022)
Researchers interviewed a diverse group of employees to gain insights into their experience of inclusion in the workplace. They found that inclusive leaders are skilled at creating voice space — an environment in which employees feel confident about openly communicating their ideas, recommendations, concerns, or other work-related opinions. Based on their study, the researchers offer four ways leaders can create voice space while elevating the confidence of their team members.